Keefektifan ekstrak daun kecubung (Datura metel L.) dalam menghambat penetasan dan siklus hidup Aedes aegypti L. - Martini, Martini; Astriana, Novi; Yuliawati, Sri; Hestiningsih, Retno; Purwantisari, Susiana (Jurnal Entomologi Indonesia, 2018)
Datura metel L. is a type of shrub that has a wooden stem, hard, and thick. Datura leaves contain chemical compounds alkaloids, saponins, flavonoids, and phenols. Based on the chemical content, datura leaves potentially as an alternative insecticide that can replace the use of synthetic insecticides. The use of synthetic insecticides in controlling the Aedes aegypti L. population has had a negative impact, such as environmental pollution, public health problems, and vector resistance. The purpose of this study was to study the effect datura leaf extract as a biochemical insecticide on inhibiting egg hatching and life cycles of Ae. aegypti. The research was conducted at Entomology Laboratory, Public Health Faculty, Universitas Diponegoro. This type of research was a true experiment with four replications and with concentration treatment i.e. 125, 250, 500, 750, 1000, and 1250 ppm. The subjects of this study were egg fertile of Ae. aegypti which were 25 eggs in each container and the total number of samples was 800 eggs. The used method for extraction was maceration. The result of probit analysis showed the activity of amethyst extract insecticide with LC50 = 199.34 ppm and LC90 = 749.08 ppm. The result of ANOVA showed a difference in the average number of non-hatching eggs due to exposure of datura leaf extract (P = 0,001). The percentage of Ae. aegypti egg hatching failure was lowest at concentration 125 ppm (41%) and the highest was at concentration 1250 ppm (98%). The survival of larvae, pupa, and mosquitoes was highest at concentration 125 ppm (49.18%, 55.17%, and 43.75% respectively). In conclusion, the datura leaf extracts potentially as a biochemical insecticide that inhibits eggs hatching and life cycles of Ae. aegypti.